Partial replacement of coarse aggregate with porcelain granite tile waste (PGTW) in reinforced concrete beam - Tan, Wen Chong (2016)
The demand of concrete in the construction industry increased rapidly due to the continuous development of countries around the globe. Extensive use of concrete leads to sacristy of natural aggregates. The reuse of construction waste and solid waste from manufacturing is an alternative way to preserve waste management problem as well as to reduce the depletion of natural resources. This research was conducted to investigate the flexural behaviour of partial coarse aggregate replacement with porcelain granite tile waste (PGTW) in reinforced concrete beam. In this study, PGTW was used to partial replace the coarse aggregate by 10%, 20% and 30%. All the concrete was design to strength of 25 N/mm2 and all the specimens were cured for 7 days and 28 days. Compressive strength test was conducted to determine the compressive strength of hardened concrete. The results presented that 10% and 20% of PGTW concrete had higher compressive strength as compared to control concrete. For flexural behaviour, all the PGTW reinforced concrete beams behaved in the same way as control reinforced concrete beam in term of load and deflection.